A national role delineation study of clinical nutrition managers and relationships with educational needs and self-efficacy - Howells, Amber (Kansas State University, 2015)
Management responsibilities in the dietetics profession are typically aligned with foodservice operations. Clinical Nutrition Managers (CNMs) are registered dietitians with administrative responsibilities for clinical nutrition services within a healthcare facility. However, no studies have clearly delineated the current responsibilities of CNMs or their level of educational preparedness for this important role. Conceptually, a gap exists between the necessary skills and knowledge required for CNMs. Focus groups, cognitive interviews, and pilot testing were used to develop an audit instrument to measure CNM practice. This audit included 84 tasks in eight job categories. The instrument was distributed online to a national sample of CNMs to assess their involvement, education preparedness, and gaps in education needed for the role. The relationships between responsibilities, educational preparedness, and self-efficacy to perform the job were investigated. Of the 84 tasks, 73 were deemed core activities [80% of CNMs (n=214) were involved in some capacity]. Significant differences were found in frequency of involvement based on size of facility (number of patient beds) and employer type. Generally, CNMs perceived importance of receiving education higher for a majority of the tasks (80 of 84). Mean scores for the level of educational needs met varied more between tasks. Clinical nutrition managers rated educational needs being met lowest for tasks within the managing financial resources category. Gap analyses revealed that the highest educational priorities were for ensuring compliance with regulations and managing human and financial resources. Categorical self-efficacy was predicted by both the educational gap and educational preparedness for some categories. Significant predictors for overall self-efficacy were the self-efficacy of the general (β = 0.203, p=0.007) and managing financial resources (β = 0.178, p=0.014) categories. Significant differences were found in overall self-efficacy based on education level [F(3, 209) = 3.881, p=0.010] and length of employment as a CNM [F(4, 208) = 7.517, p<0.001]. This research can serve as a current benchmark for CNM practice. Results allow educators, managers, and the professional association to better inform students and practitioners about the leadership role. These findings may also assist others in creating leadership development programs, certificates, or graduate degree options specific for CNMs.
Keywords: Dietetics; Clinical nutrition management; Self-efficacy; Role delineation